ANALISIS GAYA KEPEMIMPINAN PENGUSAHA FOTOKOPI REJEKI MANDIRI - FAREL VANDANO HISKIA SEBAYANG; FAUZIAH INDIRA SIREGAR; MUHAMMAD HAFIZ SIDDIQ; YULAN MARCELIA BANJARNAHOR (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the leadership style applied by the owner of the MSME Fotokopi Rejeki Mandiri in Medan and its impact on employee performance and business sustainability. The research employs a qualitative method using direct interviews with the owner and employees. The results show that the business owner implements a transformational leadership style as proposed by Bernard M. Bass, which includes four main aspects: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The owner demonstrates active involvement in operational activities, provides motivation, encourages innovation, and pays personal attention to employees’ needs. The application of transformational leadership has proven effective in increasing employee loyalty, strengthening harmonious work relationships, and maintaining business competitiveness amid technological changes and market dynamics. However, improvement is still needed in the area of digital adaptation for the business to grow more competitively. Thus, transformational leadership serves as a crucial factor in sustaining the existence and continuity of MSMEs in the modern era.